Making Otherness Accessible Functionality and Skopos in the Translation of New Testament Texts - Nord, Christiane (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractAfter describing a translation process under the condition of “split competence,” the article analyzes cases of cultural distance, drawing on the author’s experience in the translation of New Testament texts. A functional translation which strives after making the otherness of these texts accessible to modern readers, has to carefully define the skopos and the addressed audience, in order to give translation decisions a solid foundation. After the discussion of a number of examples from the New Testament, the author ventures to conclude that the functional translation of these texts can be considered a paradigmatic case of translation in general and that translation competence is not essentially linked to a language-and-culture pair.